PENGARUH ATTRIBUTE BRANDS TERHADAPKEPUTUSANPEMBELIANSEPATUBATA :Survei pada Pembeli Sepatu Bata Distrik 571 Bandung - Susilawati, - (2009)
Free market will held soon even for ASEAN, Pacific Asia or around the wor1d. One of Indonesia's competitive commodities is shoes industry. There are some serious challenges faced by industry includes hard competition between seller in getting a lot of consumers. Now Bala as familiar shoes industry in Indonesia is decreasing. It can be appeared from its market share such as district 571 in Bandung. It is because of too many new marks with new interesting products and too many import products like from China with cheaper price. All policies are used to solve this problem. And one of them is attribute brands which believed will increase amount of consumers. This research is done for analyzing the influence of attribute brands towards Bala shoes selling. Attribute brands with free variable (X} has five dimensions like price, quality, unique, limitation and service. While its relational variable (Y) consists of four dimensions, they are product choice, product ways' choice, time and number of selling. Population achieved by the researchers is 17.888 persons with 120 of them are taken. The object is Bata shoes seller district 571 in Bandung. This research is conducted for about less than one year using cross sectional. From the result through hypothesis known that attribute brands has ·positive influence towards selling decision.